PENGARUH PEMERIKSAAN KEHAMILAN TERHADAP KEJADIAN BAYI BERAT LAHIR RENDAH (BBLR) DI KELURAHAN GEDUNG JOHOR KOTA MEDAN - Bancin, Dewi R; Sitorus, Friska; Anita, Surya (Jurnal Reproductive Health, 2022)
LBW is a baby with a low birth weight or less than 2500 grams, birth weight is a good predictor for the baby's growth and survival. A term baby is generally born weighing 2500 grams or more. LBW is one of the risk factors that contributes to infant mortality, especially in the perinatal period. The incidence and mortality of LBW due to complications such as asphyxia, infection, hypothermia, hyperbilirubinemia is still high (Indrayani, 2015). This study aims to see whether there is an effect of maternal examination visits during pregnancy with the incidence of LBW with analytic observational research and cross sectional research design. The number of samples in this study was 48 people consisting of postpartum mothers who gave birth to LBW or not, the results showed that there was a relationship between maternal eating patterns during pregnancy and the incidence of LBW where the PV value (0.03), this study recommends that every pregnant woman routinely to check her pregnancy and to health workers to always provide health promotion about the importance of check-up visits